Double fault distinguishability in linear systems - Kościelny, Jan Maciej; Łabęda-Grudziak, Zofia M. (Zielona Góra: Uniwersytet Zielonogórski)
This paper develops a new approach to double fault isolation in linear systems with the aid of directional residuals. The method of residual generation for computational as well as internal forms is applied. Isolation of double faults is based on the investigation of the coplanarity of the residual vector with the planes defined by the individual pairs of directional fault vectors.
Keywords: faults isolation; double fault; fault distinguishability; directional and structured residuals; secondary residuals; linear systems